The biopolitical turn in educational theory: Autonomist Marxism and revolutionary subjectivity in Empire. Issue 7 (7th June 2022) - Bourassa, Gregory N.; Slater, Graham B.
Abstract: With Empire, Michael Hardt and Antonio Negri reinvigorated debates in political theory and radical philosophy about the cultivation of revolutionary subjectivity. Their theorization of Empire and multitude has also significantly affected the tenor of critical approaches to educational theory during the past two decades. In this article, we discuss Hardt and Negri's contribution to what we call the biopolitical turn in educational theory, emphasizing the influence of autonomist Marxism on their work. Even more specifically, we discuss the impact of the autonomist tradition on their formulation of the nature of the relationship between the multitude and Empire: that the multitude is the generative force of the social world, whereas Empire is merely an apparatus of capture. This autonomist approach reveals a set of questions regarding subjectivity, materialism, and social ontology, which we argue are ripe for engagement by educational theorists, and indicate the enduring relevance of Empire as a valuable text for educational theorists interested in matters of biopolitical production, collective opposition, and revolutionary subjectivity.